2020
DOI: 10.1177/1420326x20975835
|View full text |Cite
|
Sign up to set email alerts
|

Moisture buffering effect of hygroscopic materials under wall moisture transfer

Abstract: Hygroscopic material can moderate the indoor humidity variation due to its moisture buffering effect. This effect would change when used as interior finish mainly due to air exchange and wall moisture transfer. The author focused on clarifying the extent of the wall'’s influence on indoor moisture buffering and building humidity environment. A room model was established and the situation of no wall moisture transfer was simulated by adding a vapour barrier between the interior finish and the wall. Comparing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The result relates to increased ventilation on the building envelope’s hygroscopic materials when opening doors. Some studies 46 have shown that high ventilation rates affect the moisture buffering effect of building envelope’s hygroscopic materials, thus increasing fluctuations in indoor relative humidity, but it also contributes to more indoor moisture removal, which helps to reduce indoor relative humidity and increases the optimal RH period (40–60%). Therefore, opening the door was conducive to indoor moisture removal and maintaining a comfortable humidity level, especially when the RH of the outdoor air was low.
Figure 13.Variations in indoor and outdoor RH of the Kim-shaped house under open- and closed-door working conditions.
…”
Section: Resultsmentioning
confidence: 99%
“…The result relates to increased ventilation on the building envelope’s hygroscopic materials when opening doors. Some studies 46 have shown that high ventilation rates affect the moisture buffering effect of building envelope’s hygroscopic materials, thus increasing fluctuations in indoor relative humidity, but it also contributes to more indoor moisture removal, which helps to reduce indoor relative humidity and increases the optimal RH period (40–60%). Therefore, opening the door was conducive to indoor moisture removal and maintaining a comfortable humidity level, especially when the RH of the outdoor air was low.
Figure 13.Variations in indoor and outdoor RH of the Kim-shaped house under open- and closed-door working conditions.
…”
Section: Resultsmentioning
confidence: 99%
“…Two types of indicators were defined to quantify how much of the buffering effect was created at a given macroenvironment fluctuation. Equation ( 10) is the absolute reduction of fluctuation, respectively, for temperature buffering (TB) [°C] and equation (11) is the humidity buffering (HB) [% RH]:…”
Section: Measurement For Water Vapour Diffusion Coefficientmentioning
confidence: 99%
“…Buildings with a large thermal mass and hygroscopic inertia, producing airtight and thermally insulated envelopes, impede heat and mass transfer between outdoor and indoor, thus stabilising the indoor environment. [9][10][11] In general, the buildings which provide low energy operation for collection storage have three features for passive environmental control, 'high thermal resistance value and energy storage capacity', 'good building airtightness' and 'effective absorption dehumidification'. [12][13][14] Due to the passive environmental control, the indoor air temperature and relative humidity can be maintained within the comfort zone while the total energy consumption falls by 69.2% in a measured winter.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Controlling relative humidity is crucial for maintaining building longevity, ensuring proper storage conditions, and minimizing energy usage [15][16][17]. Humidity control materials (HCM) are porous materials that can regulate ambient humidity and temperature without external power or mechanical equipment.…”
Section: Introductionmentioning
confidence: 99%